Monthly intravitreal bevacizumab for macular edema after iodine-125 plaque radiotherapy of uveal melanoma - Arman Mashayekhi (2018)
Purpose: To examine the efficacy of monthly injections of intravitreal bevacizumab (IVB) for macular edema after iodine-125 plaque radiotherapy of uveal melanoma. Methods: We studied 36 patients with macular edema after plaque radiotherapy of uveal melanoma in this noncomparative, interventional case series. All eyes were treated with 4 monthly injections of IVB. Central macular thickness (CMT) and best-corrected visual acuity (BCVA) were measured before each injection and 4-6 months after the first injection. The main outcome measures were change in CMT and BCVA. Results: At 4-6 months following the first IVB, 20 eyes (56%) had decreased CMT, 11 eyes (31%) had stable CMT, and 5 eyes (14%) had increased CMT. The mean change in CMT and the mean percent change in CMT at 4-6 months compared to baseline were -91 μm (-20%) in all eyes, -174 μm (-37%) in the group with decreased macular thickness, -14 μm (-3%) in the group with stable macular thickness, and +69 μm (+17%) in the group with increased macular thickness. At 4-6 months, 15 eyes (42%) had increased BCVA, 16 eyes (44%) had stable BCVA, and 5 eyes (14%) had decreased BCVA. An increase in CMT was seen between the fourth monthly IVB injection and the final evaluation at 4-6 months after the first injection in all 3 groups of our study. Conclusions: At 4-6 months following the first injection, 4 monthly injections of IVB in eyes with macular edema after plaque radiotherapy of uveal melanoma decreased macular edema in 56% and improved BCVA in 42% of the treated eyes. © 2013 Wichtig Editore.